A systematic review and bioinformatics study on genes and micro-RNAs involving the transformation of endometriosis into ovarian cancer - Sheikhvatan, Mehrdad; Chaichian, Shahla; Moazzami, Bahram (MicroRNA, 2020)
Background: Along with the description of tumorigenesis processes in endometriosisrelated - ovarian cancer, identifying dysregulated miRNAs, the tar...
Gesehen am 15.04.2020